Oxford Classification of IgA Nephropathy Is Applicable to Predict Long-Term Outcomes of Henoch-Schönlein Purpura Nephritis - Hamid Nasri (Iranian Journal of Allergy, Asthma and Immunology, 2014)
Henoch-Schönlein purpura nephritis and IgA nephropathy are currently considered to be different clinical presentations of the same disease. There is need for a reliable proven, morphologic classification that can help clinicians more accurately formulate treatment strategies for patients with Henoch-Schönlein purpura nephritis. Considering that Henoch-Schönlein purpura nephritis and IgA nephropathy have common characteristics of pathogenesis and histopathologic findings, we postulate that, the Oxford classification could also help predict long-term outcomes in Henoch-Schönlein purpura nephritis. Hence, we suggest to applicate the Oxford classification for patients with Henoch-Schönlein purpura nephritis.